EFFECTS OF SECRETABLE PLACENTAL FACTORS UPON SECRETION OF CYTOKINES BY THP-1 MONOCYTE-LIKE CELLS - Ya. S. Onokhina; T. Yu. Lvova; D. Z. Tzitzkarava; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2014)
Abstract. Мonocytes in feto-placental circulation are exposed to factors secreted by placental tissue. These factors influence monocyte functions in pregnancy. In present study, an in vitro model (monocyte-like THP-1 cells) was used for assessing effects of soluble placental factors obtained from women with physiological pregnancies, or preeclampsia cases. The following effects of placental factors were revealed: increased secretion of VEGF by THP-1 cells along with decreased secretion of IL-6, IL-8 and MCP-1 under the influence of placental factors from the I. trimester of pregnancy in comparison with III. trimester. Secretion of IL-6 and MCP-1 by THP-1 cells was increased, and secretion of soluble TNFRII was decreased upon co-cultivation with soluble placental factors from the women with preeclampsia, as compared with placental products from physiological pregnancies.The work is supported by grants ГК № 02.740.11.0711 from Ministry of Education and Science, and НШ-3594.2010.7 grant from the President of Russian Federation.